1976
DOI: 10.1177/030098587601300208
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hyalinosis in Dogs

Abstract: Pulmonary hyalinosis occurred in Beagles exposed to radon daughters with uranium ore dust. The lesion was composed of alveolar cells distended with material positive for periodic acid-Schiff (PAS) and oil red O that ultrastructurally consisted of a whorled arrangement of lamellar membranes suggestive of a storage disease. The high incidence in exposed dogs and the ultrastructural appearance suggested the material originated endogenously as a degenerative response to injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…5 The other study found lesions in 30 of 34 beagles exposed to airborne radon daughters (radioactive decay particles) with uranium ore dust and attributed the material to a degenerative response to injury with accumulation of endogenous secretions. 10 All but 1 of the affected EIII/JC described here were unmanipulated breeders, with no known airborne exposures (no history provided for the exception). Only 1 rabbit had upper airway disease potentially causing obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…5 The other study found lesions in 30 of 34 beagles exposed to airborne radon daughters (radioactive decay particles) with uranium ore dust and attributed the material to a degenerative response to injury with accumulation of endogenous secretions. 10 All but 1 of the affected EIII/JC described here were unmanipulated breeders, with no known airborne exposures (no history provided for the exception). Only 1 rabbit had upper airway disease potentially causing obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…8), involving larger areas, were palpated at gross examination. Dagle et al (Da76) described a lesion similar to the pulmonary hyalinosis that occurred in the dogs of Groups 1 and 2 as cellular degradation because of its ultrastructural appearance. Vesicular emphysema was present in the lungs of all dogs from Groups 1 and 2.…”
Section: Group 3 (Cigarette Smoke Only)mentioning
confidence: 99%
“…3 Early descriptions suggested a response to inhalation or aspiration of irritants, including uranium ore dust. 4 Similar to other alveolar-filling disorders, abnormal alveolar hyaline material is thought to accumulate because of some combination of reduced bronchociliary clearance, excessive production, or impaired breakdown, typically by alveolar macrophages.…”
mentioning
confidence: 99%
“…The bodies also display birefringence under polarized light. 1,4 The inciting cause and pathogenesis for this accumulation of pulmonary hyaline material is unknown, but disease is seen predominantly in older dogs and typically is considered incidental. 3 Early descriptions suggested a response to inhalation or aspiration of irritants, including uranium ore dust.…”
mentioning
confidence: 99%
See 1 more Smart Citation